ANALISIS FAKTO-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI SAWAH DESA SETIRIS KECAMATAN MUARO SEBO KABUPATEN MUARO JAMBI - Sudirman Sudirman; Hasminidiarty Hasminidiarty (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
The economic structure ofJambiProvinceis characterized by the role of each sector, such as agriculture, service sector, industrial sector and other sectors. The agricultural sector plays an important role in improving and expanding employment opportunities, therefore this sector can not be ignored altogether. Sebahagian small agricultural production is done by small farmers and their scattered locations inJambiProvince. This sector plays an important role in enhancing regional economic growth Jambi. One of the products sub-sector of agriculture is rice paddies. Basically rice is a commodity that has a very important role for the economic development area of Jambi. The contribution of rice to the local income Jambi also great. In addition, rice is still acting as a source of livelihood of farmers in some regions including the District of Jambi province Jambi Muaro. Muaro Jambi is one area where most inhabitants live in the countryside and live as farmers. As for agricultural crops cultivated in the district of Jambi is Muaro Food crops (rice, rice), crops and fruit plantations. Increasing rice production can be done on agricultural land that has been developed.